Principal's Leadership in Responding to The Reform of Indonesian Education: Studi in Elementary School 1 South Tangerang - Firman Mansir (Cetta: Jurnal Ilmu Pendidikan, 2023)
The principal in elementary school as a leader in an educational institution organization in Indonesia has a very strategic role. The existence of educational institutions is one of the important points to advance the Indonesian nation so a school principal has a burden and responsibility that must be shouldered because the principal has a hand in every renewal of Indonesian education. The purpose of this study was to determine the leadership responsibilities of the principal of Elementary School 1 South Tangerang to education reform, especially in Indonesia. This research uses a qualitative approach method in collecting data through literature studies that use data sources from International and National Journals as well as several relevant research results. The results of this study show that there is a big role that can be done by school principals in responding to the renewal of Indonesian education, one of which is by preparing and improving facilities and infrastructure in educational institutions and providing modern learning tools in the spirit of learning in the 21st century. Thus, the principal has a major contribution to realizing 21st-century learning which is part of the renewal of Indonesian education, so without his leadership, it will be difficult to realize an enlightened Indonesian education.